Antioxidant Activity Test of Ubiquinone Microemulsion with DPPH (1,1-Diphenyl-2-picrylhydrazyl) Method : Uji Aktivitas Antioksidan Mikroemulsi Ubiquinone dengan Metode DPPH (1,1-Difenil-2-pikrilhidrazil) - Silvi Ayu Wulansari; Umarudin; Floreta Fiska Yuliarni (Akademi Farmasi Surabaya, 2022)
Ubiquinone is an antioxidant formulated in cosmetic preparations. It is necessary to test the atioxidant activity to ensure the quality of the preparation. The purpose of this study was to determine the antioxidant activity of the ubiquinone formulated in microemulsion preparations. The Ubiquinone were formulated into mikroemultion with cocentrations 0.25%, 0.5%, 0.75% and 1%, separately. The DPPH method was selected as the atioxidant activity test.. The data analysis in this study was descriptive to determine the IC50 value of ubiquinone microemulsion preparations F1, F2, F3 and F4 and ubiquinone as a comparison. The result shows that the antioxidant value of IC50 ubiquinone microemulsion of F1, F2, F3, and F4 are 56.48 ppm, 49.92 ppm, 32.76 ppm, and 20.71 ppm, respectively. The average value of ubiquinone microemulsion is 59.16 ppm. This research concludes that the microemulsion formula F1-F4 of ubiquinon has a very strong antioxidant activity compared to ubiquinone.